ReGroup: Interactive Machine Learning for On-Demand Group Creation in Social Networks - Amershi, Saleema; Fogarty, James; Weld, Daniel (Proceeding CHI '12 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2012)
We present ReGroup, a novel end-user interactive machine learning system for helping people create custom, on-demand groups in online social networks. As a person adds members to a group, ReGroup iteratively learns a probabilistic model of group membership specific to that group. ReGroup then uses its currently learned model to suggest additional members and group characteristics for filtering. Our evaluation shows that ReGroup is effective for helping people create large and varied groups, whereas traditional methods (searching by name or selecting from an alphabetical list) are better suited for small groups whose members can be easily recalled by name. By facilitating on-demand group creation, ReGroup can enable in-context sharing and potentially encourage better online privacy practices. In addition, applying interactive machine learning to social network group creation introduces several challenges for designing effective end-user interaction with machine learning. We identify these challenges and discuss how we address them in ReGroup.